Long-term changes in gingival recessions and their impact on oral health-related quality of life in patients under supportive periodontal therapy: a bidirectional cohort study - Sonnenschein, Sarah K.; Ziegler, Philipp; Kim, Ti-Sun (Quintessence international, 2025)
Objectives: To evaluate changes in gingival recessions in periodontitis patients over 10 years of supportive periodontal therapy and to assess the impact of gingival recession on oral health-related quality of life (OHRQoL). Method and materials: Fifty-one patients with over 10 years of supportive periodontal therapy were followed up (V1) with complete periodontal status including periodontal probing depth (PPD) and clinical attachment level (CAL) at six sites/tooth, oral hygiene indices, and recession status. Patient anamnesis, oral hygiene habits, and orthodontic history were assessed. Data were compared with records from 10 to 11.5 years prior (VO). Gingival recession changes were analyzed at patient level, and for all teeth with deep gingival recession >= 3 mm at tooth and site level (midbuccal site). OHRQoL was assessed at V1 (OHIP-G14 questionnaire). Possible risk factors for gingival recession progression and the associations between the number of deep gingival recession and OHRQoL were tested (linear mixed-ef fects models, linear regression). Results: The analysis included 45 patients (stage III/IV periodontitis). Patients retained most teeth (VO, 23.87 +/- 4.38; V1, 22.53 +/- 4.78), with stable mean over- all PPD (VO, 2.34 +/- 0.35 mm; V1, 2.39 +/- 0.26 mm) , CAL (VO, 3.56 +/- 0.94 mm; V1, 3.56 +/- 0.89 mm). Teeth with deep gingival recessions showed overall only minimal mean gingival reces- sion progression (0.16 +/- 0.97 mm). The mean increase at the midbuccal sites was 0.66 +/- 1.58 mm. In total, 25% of teeth had >1 mm gingival recession progression at the midbuccal site. Molars showed less gingival recession progression than anterior teeth. The number of deep gingival recessions did not signifi- cantly impact OHRQoL. Conclusions: Periodontitis patients on regularsupportive periodontal therapy showed high periodon- tal stability with minimal gingival recession progression. The number of deep gingival recessions was not associated with OH ROoL. (Quintessence Int 2025;56:186-196;